Application of last planner system with BIM in construction plan management - Liu, Wenming; Xie, Hongdong; Peng, Guoping; Wang, Shiping (International Journal of Engineering and Technology, 2021)
The project team maintains workflow continuity as much as possible to deliver products on time. Nevertheless, poor construction management makes the workflow unstable during the construction process, which leads to the delayed delivery of the building. As different methods to improve production efficiency, Lean Construction and Building Information Modelling (BIM) have a positive impact on the industry. Although many researches have shown the unique advantages of the Last Planner System (LPS) and BIM Technology, the advantages of their integration have not been fully exploited. This paper explores the application of the LPS and BIM in the construction phase through a project that transforms from traditional construction process planning to the use of the LPS. The project results show the impact of the LPS and BIM as lean methods on the project, which can improve the workflow of the construction project by improving efficiency and coordination.Â Â